Burkina Faso : Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Progress toward growth objectives suffered from exogenous shocks. A substantial improvement was observed in certain social indicators, particularly in the health and education sectors. The Poverty Reduction Strategy Paper (PRSP) is reputed to be a framework for convergence of all interventions in Burkina Faso. The priority program should be extended to sectors that will have a clear impact on poverty. For successful implementation of the PRSP, it is important to emphasize the formulation of sectoral policies and to implement a national capacity-building plan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet